TRANSFER PRICING AND TAX AGGRESSIVENESS IN MULTINATIONAL COMPANIES BEFORE AFTER THE TAX AMNESTY PROGRAM - Olivi Sabilla Sa'dani (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2021)
The Tax Amnesty in Indonesia of 2016 aims to increase tax revenue, which will be used to finance development. Tax Amnesty is also expected to reduce transfer pricing practice by holding a period of recognition of assets for a minimum of three years to increase domestic liquidity and domestic investment. In comparison, transfer pricing itself will affect a company's tax aggressiveness. The purpose of this study is to examine the effect of transfer pricing and tax aggressiveness before and after the tax amnesty policy. This study uses secondary data in annual reports of a multinational company registered on the Indonesia Stock Exchange from 2014 to 2019. The method of determining the sample is purposive sampling, the selection of models based on specific criteria. The method of analysis of this research is non-parametric approaches. The results of this study indicate the difference in transfer pricing before and after the tax amnesty policy. At the same time, there is no difference in the level of tax aggressiveness before and after the tax amnesty.